Hiperpotasemia refractaria: su fisiopatología y tratamiento - Musso, Carlos Guido; Aguilera Diaz, Jerónimo; Vilas, Manuel; Badolato, María; Bonetto, Alberto; Luna, Daniel; Algranati , Luis; Jauregui, Ricardo (Revista del Hospital Italiano de Buenos Aires, 2010)
.